GENERAL WELFARE IMPROVEMENT THROUGH OPTIMIZATION OF HAJJ FUNDS WITH PRODUCTIVE WAQF - Vidya Nurchaliza; Wirdyaningsih Wirdyaningsih (Proceedings of AICS - Social Sciences, 2019)
Productive waqf is a very strategic economic instrument to realize welfare. However, this potential has not been maximally utilized because waqf organizers have difficulties in finding funds to increase investment in waqf assets. On the other hand, the Hajj Financial Management Agency (BPKH) is given the mandate to manage hundreds of trillions of Hajj funds. Law No. 34 of 2014 regulates the financial management of Hajj based on sharia principles that aim to increase the welfare of the people. The Waqf Law also mandates the management of waqf assets to improve public welfare. So that, it is the right thing to do cooperation between BPKH and waqf organizer (nazhir). In this study, the approach method used is a juridical-normative method to study the management of Hajj funds with productive waqf in terms of law and concept. Therefore, the purposes of this research are to review the laws and schemes in the collaboration. The research concludes: first, the synergy between Hajj funds and productive waqf can be done legally and second, the method that can be used by BPKH in placing Hajj funds with productive waqf schemes is profit sharing collaboration contract (Mudharabah) or Sukuk waqf.